The research of fluorescent lamps’ luminous efficiency depending on their constructions - Басова, Юлія Олександрівна (Technology audit and production reserves, 2013)
The luminous efficiency of compact fluorescent lamps was studied in the article depending on the quantity of lamps’ channels and the distance between them. The model, which considers multiple reflections between the parallel placed channels, was used for theoretical analysis of the impact of quantity of lamps’ channels on the luminous efficiency of compact fluorescent lamps. These multiple reflections lead to the loss of luminous flux. The analyzed model can be used not only to assess the efficiency of compact fluorescent lamps that have its channels placed in the same plane, but also to evaluate the construction of compact fluorescent lamps that have spatial arrangement of channels. It was shown that the luminous efficiency decreases when the number of channels increase and the distance between them reduces. When increasing the distance between the channels for more than three diameters the efficiency of compact fluorescent lamps does not reduce significantly (approximately 2-3%). In some cases, these losses can be neglected. The experimental verification of the worked out model was done. Flux measurements were done on individual fluorescent lamps rated at 4 watts. Those lamps were combined by 2, 4, 6 and 8 pieces. The lamps were placed the same way with 2, 4, 6 and 8-channel tubes. The results of experiment indicate that the luminous efficiency of multi compact fluorescent lamps is reduced by 2-4% due to multiple reflections. This means that the difference between the calculated and experimental results is less than 5%. The proposed model can be used for engineering calculations while testing compact fluorescent lamps